Respostas
respondido por:
1
Sabemos que:
f(x) = ax + b
A = (1, 5) / B = (-3, -7)
Calculando "a":
a = ∆y/∆x
a = y(B) - y(A)/x(B) - x(A)
a = (-7 - 5)/(-3 - 1)
a = -12/-4
a = 3
f(x) = 3x + b
Calculando "b":
5 = 3.1 + b
b = 5 - 3
b = 2
Portanto:
f(x) = 3x + 2
f(x) = ax + b
A = (1, 5) / B = (-3, -7)
Calculando "a":
a = ∆y/∆x
a = y(B) - y(A)/x(B) - x(A)
a = (-7 - 5)/(-3 - 1)
a = -12/-4
a = 3
f(x) = 3x + b
Calculando "b":
5 = 3.1 + b
b = 5 - 3
b = 2
Portanto:
f(x) = 3x + 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás